Silicon-carbon composite nanomaterial and application thereof in lithium ion battery

By preparing silicon-carbon composite nanomaterials with porous structures, the problem of expansion and rupture of the negative electrode material of lithium-ion battery during charging and discharging is solved, high specific capacity and good cycle stability are achieved, and the overall performance and safety of the battery are improved. .

CN119230776AInactive Publication Date: 2024-12-31JIANGSU LEINA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411199340.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The negative electrode material of lithium-ion battery is prone to expand and rupture during charging and discharging, affecting battery life.

Method used

Silicon-carbon composite nanomaterials composed of silicon nanoparticles, carbon sources and pore-forming agents are made of wet mechanical ball milling and heat treatment to form a porous structure to alleviate volume expansion and combine an optimized electrolyte and diaphragm design.

Benefits of technology

It significantly improves the specific capacity and cycle stability of lithium-ion batteries, extends battery life, and improves charging and discharging performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230776A_ABST
    Figure CN119230776A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite nanomaterial and application thereof in a lithium ion battery, the silicon-carbon composite nanomaterial is composed of silicon nanoparticles, a carbon source and a pore-forming agent, the silicon nanoparticles, the carbon source and the pore-forming agent are subjected to wet mechanical ball milling and mixing to form a porous structure material, and in the application of the lithium ion battery, the material is used as a negative electrode material, and is used as a negative electrode material. The specific capacity under the current density of 1 A / g exceeds 750 mAh / g, and the capacity is kept to be higher than 85% after 500 times of charge-discharge cycles; through the application of the material in the lithium ion battery, the optimal cooperation of high capacity, high current and cycling stability is realized, and the performance of the lithium ion battery is further optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano material application, and in particular relates to a silicon-carbon composite nano material and its application in a lithium ion battery. Background Art

[0002] With the continuous advancement of science and technology, lithium-ion batteries, as an important energy storage technology, have been widely used in electric vehicles, portable electronic devices and other fields. Improving the performance of lithium-ion batteries, such as energy density, specific capacity and cycle stability, has become the focus of current research.

[0003] Silicon is an ideal negative electrode material due to its high theoretical capacity, but it is easy to expand and crack during the charge and discharge process, which affects the battery life. To solve this problem, silicon-carbon composite materials, as an innovative solution, have demonstrated superior performance. By introducing carbon sources and pore-forming agents, combined with wet mechanical ball milling and heat treatment processes, the prepared silicon-carbon composite nanomaterials can significantly improve the specific capacity and cycle stability of lithium-ion batteries. Such materials not only have a large specific surface area and excellent porous structure, but also can effectively alleviate the volume expansion problem of silicon, thereby improving the overall performance of the battery. Summary of the invention

[0004] The purpose of the present invention is to provide a silicon-carbon composite nanomaterial and its application in lithium-ion batteries in order to solve the problem that the existing lithium-ion battery negative electrode materials are prone to expansion and rupture during the charge and discharge process, which affects the battery life.

[0005] The present invention achieves the above-mentioned purpose through the following technical scheme: a silicon-carbon composite nanomaterial, which is composed of silicon nanoparticles, a carbon source and a pore-forming agent, and is prepared by wet mechanical ball milling and then heat-treated;

[0006] The volume fraction of the silicon nanoparticles is 20% to 80%;

[0007] The carbon source is one or more selected from glucose and sucrose;

[0008] The pore-forming agent is guanidine carbonate, and its volume fraction is 1% to 10%;

[0009] The heat treatment is performed in nitrogen, argon or hydrogen at a temperature ranging from 600°C to 1200°C.

[0010] Furthermore, the silicon-carbon composite nanomaterial has a porous structure with a pore size ranging from 2 nm to 50 nm and a porosity of 30% to 70%.

[0011] Furthermore, the wet mechanical ball milling time is 1 hour to 10 hours, and when the heat treatment is performed using nitrogen or argon, the temperature range is 800°C to 1000°C.

[0012] The invention discloses an application of a silicon-carbon composite nano material in a lithium-ion battery. The negative electrode of the lithium-ion battery adopts the silicon-carbon composite nano material, and the positive electrode of the lithium-ion battery adopts an electrolyte and a diaphragm.

[0013] Furthermore, the specific capacity of the silicon-carbon composite nanomaterial of the negative electrode is higher than 750 mAh / g at a current density of 1 A / g, and the capacity retention rate is higher than 85% after 500 charge and discharge cycles.

[0014] Furthermore, the electrolyte of the lithium-ion battery is composed of 1 M lithium salt dissolved in a mixed solvent of dimethyl carbonate and ethylene carbonate.

[0015] Furthermore, the diaphragm is made of polyolefin material and has the following characteristics:

[0016] a. The thickness of the diaphragm ranges from 10 μm to 30 μm;

[0017] b. The pore size distribution of the diaphragm is between 0.5 μm and 2 μm;

[0018] c. The diaphragm has excellent mechanical strength, and its breaking strength is not less than 5 MPa.

[0019] Beneficial effects: The invention has reasonable design, simple and stable structure, strong practicability, and has the following advantages:

[0020] 1. The low-cost, high-yield ball milling technology combined with post-heat treatment can achieve controllable construction of silicon-carbon composite materials in terms of morphology, structure, properties, etc., which is conducive to changing its electrochemical properties as an electrode material for lithium-ion batteries;

[0021] 2. By adjusting the production parameters, silicon nanoparticles of different sizes can be used to study the effect of the size of silicon-carbon negative electrode materials on battery performance and adjust the different lithium-ion battery requirements;

[0022] 3. In the prepared silicon-carbon composite material, carbon coating can effectively alleviate the volume expansion effect of silicon and improve the cycle life of the electrode material. The conductive network composed of carbon materials can quickly conduct electrons to silicon nanoparticles, improving the electrical contact of silicon nanoparticles. The porous structure formed inside constructs a channel that is conducive to lithium ion transmission, which can improve the rapid charging and discharging performance of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the preparation process structure of the present invention. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0025] Embodiment 1:

[0026] Combination Figure 1 As shown, a silicon-carbon composite nanomaterial is composed of silicon nanoparticles, a carbon source and a pore-forming agent, and is prepared by wet mechanical ball milling and then heat treatment;

[0027] The volume fraction of silicon nanoparticles is 20% to 80%. Silicon nanoparticles have a high theoretical specific capacity, which helps to improve the energy storage capacity of the material;

[0028] The carbon source is one or more selected from glucose and sucrose, which are converted into conductive carbon materials at high temperatures to enhance the electrical conductivity and structural stability of the composite material;

[0029] The pore-forming agent is guanidine carbonate, and its volume fraction is 1% to 10%. Guanidine carbonate decomposes to generate gas during the heat treatment process, forming a porous structure, thereby increasing the specific surface area and porosity of the material;

[0030] The heat treatment is carried out in nitrogen, argon or hydrogen to prevent the material from oxidizing at high temperatures and maintain its chemical stability in the temperature range of 600°C to 1200°C. Temperatures in this range can optimize the conversion of the carbon source and the structural stability of the silicon nanoparticles, forming a composite material with good electrical conductivity and pore structure.

[0031] Silicon-carbon composite nanomaterials exhibit a significant porous structure with a pore size range of 2nm to 50nm, providing a rich pore network that helps to significantly improve the specific surface area and electrochemical properties of the material. The porosity is between 30% and 70%, which allows the material to have excellent charge storage capacity and conductivity while maintaining an appropriate density. Such a porous structure can not only effectively alleviate the volume change of silicon during the charging and discharging process, but also enhance the conductive path of the material, thereby improving its cycle stability and charge and discharge rate in batteries and other energy storage applications. In addition, the presence of pores also improves the permeability of the electrolyte and the efficiency of ion transfer, further optimizing the overall performance of the material.

[0032] The wet mechanical ball milling time is set between 1 hour and 10 hours. This processing time is selected to optimize the particle size and uniformity of the material and ensure effective mixing and refinement. The longer ball milling time can further break up the material particles and improve its uniformity and reactivity. The heat treatment stage uses a nitrogen or argon protective atmosphere with a temperature range of 800°C to 1000°C. This high-temperature treatment helps promote the full reaction and interaction between silicon and carbon to form a stable composite structure.

[0033] A silicon-carbon composite nanomaterial is used in a lithium-ion battery. The negative electrode of the lithium-ion battery adopts the silicon-carbon composite nanomaterial. The silicon-carbon composite material combines the high theoretical capacity of silicon and the excellent conductivity of carbon. Its porous structure helps to alleviate the volume expansion of silicon during the charging and discharging process and reduces the mechanical stress of the negative electrode material. The positive electrode of the lithium-ion battery adopts an electrolyte and a diaphragm. The electrolyte is used to provide a conductive medium between the positive and negative electrodes of the lithium-ion battery, and the diaphragm prevents direct contact between the positive and negative electrodes, thereby ensuring the safety and stable performance of the battery.

[0034] The specific capacity of the silicon-carbon composite nanomaterial of the negative electrode is higher than 750 mAh / g at a current density of 1 A / g. This high capacity value indicates that the material can store a large amount of lithium ions, thereby improving the energy density of the battery. After 500 charge and discharge cycles, the capacity retention rate is higher than 85%, showing its excellent cycle stability and durability.

[0035] The electrolyte of lithium-ion batteries is composed of 1 M lithium salt dissolved in a mixed solvent of dimethyl carbonate and ethylene carbonate. This electrolyte configuration has excellent ionic conductivity and stability, can effectively support the migration of lithium ions, and improve the conductivity and overall performance of the battery. Dimethyl carbonate as a solvent provides a lower viscosity, which helps to improve the fluidity and ion transfer rate of the electrolyte, while ethylene carbonate has high electrochemical stability, effectively inhibits the decomposition of the electrolyte, and improves the operating voltage range of the battery. This mixed solvent system not only enhances the chemical stability and cycle life of the electrolyte, but also optimizes the energy density and charge and discharge efficiency of the battery, providing a reliable guarantee for the stable operation of high-performance lithium-ion batteries.

[0036] The diaphragm is made of polyolefin material and has the following characteristics:

[0037] a. The thickness of the separator ranges from 10 μm to 30 μm. This design ensures the effective isolation function of the separator while maintaining appropriate battery volume and weight;

[0038] b. The pore size of the separator is distributed between 0.5 μm and 2 μm. This pore size range allows lithium ions to migrate smoothly between the positive and negative electrodes while preventing tiny particles of electrode materials from penetrating, thereby improving the safety and performance of the battery;

[0039] c. The diaphragm has excellent mechanical strength, and its breaking strength is not less than 5 MPa, which ensures that the diaphragm can withstand sufficient mechanical stress during the charge and discharge process, avoiding battery short circuit or performance degradation caused by diaphragm rupture. These characteristics work together to ensure the stability and reliability of the diaphragm in high-performance lithium-ion batteries.

[0040] In summary, this silicon-carbon composite nanomaterial shows significant advantages in lithium-ion batteries with its unique structure and composition. Through wet mechanical ball milling and high-temperature heat treatment technology, the material achieves excellent uniformity and stability. The high volume fraction of silicon nanoparticles and the formation of porous carbon structure not only improve the specific capacity and conductivity of the material, but also effectively alleviate the volume change of silicon during the charging and discharging process, thereby improving the cycle stability and charging and discharging rate. The pore structure of the material optimizes the permeability of the electrolyte and the ion transfer efficiency, further enhancing the overall performance of the battery.

[0041] In lithium-ion batteries, the use of this silicon-carbon composite nanomaterial as the negative electrode material enables the battery to have a high specific capacity of more than 750 mAh / g and a good cycle stability of more than 85%. At the same time, the matching 1 M lithium salt electrolyte and high-performance polyolefin separator ensure the battery's conductivity, chemical stability and safety. The optimized formula of the electrolyte and the design of the separator jointly improve the battery's energy density and charge and discharge efficiency, providing a reliable guarantee for the stable operation of high-performance lithium-ion batteries. This material system not only demonstrates excellent electrochemical properties, but also provides strong support for the development of future energy storage technologies.

[0042] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and range of equivalents of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0043] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A silicon-carbon composite nanomaterial, characterized in that: The silicon-carbon composite nanomaterial is composed of silicon nanoparticles, a carbon source and a pore-forming agent, and is prepared by wet mechanical ball milling and then heat treatment; The volume fraction of the silicon nanoparticles is 20% to 80%; The carbon source is one or more selected from glucose and sucrose; The pore-forming agent is guanidine carbonate, and its volume fraction is 1% to 10%; The heat treatment is performed in nitrogen, argon or hydrogen at a temperature ranging from 600°C to 1200°C.

2. The silicon-carbon composite nanomaterial according to claim 1, characterized in that: The silicon-carbon composite nanomaterial has a porous structure with a pore size ranging from 2nm to 50nm and a porosity of 30% to 70%.

3. The silicon-carbon composite nanomaterial according to claim 2, characterized in that: The wet mechanical ball milling time is 1 hour to 10 hours, and when the heat treatment adopts nitrogen or argon, the temperature range is 800°C to 1000°C.

4. The use of a silicon-carbon composite nanomaterial in a lithium-ion battery according to claim 3, characterized in that: The negative electrode of the lithium ion battery adopts the silicon-carbon composite nano material, and the positive electrode of the lithium ion battery adopts an electrolyte and a diaphragm.

5. The use of a silicon-carbon composite nanomaterial in a lithium-ion battery according to claim 4, characterized in that: The specific capacity of the silicon-carbon composite nanomaterial of the negative electrode is higher than 750 mAh / g at a current density of 1 A / g, and the capacity retention rate is higher than 85% after 500 charge and discharge cycles.

6. The use of a silicon-carbon composite nanomaterial in a lithium-ion battery according to claim 5, characterized in that: The electrolyte of the lithium ion battery is composed of 1 M lithium salt dissolved in a mixed solvent of dimethyl carbonate and ethylene carbonate.

7. The use of a silicon-carbon composite nanomaterial in a lithium-ion battery according to claim 6, characterized in that: The diaphragm is made of polyolefin material and has the following characteristics: a. The thickness of the diaphragm ranges from 10 μm to 30 μm; b. The pore size distribution of the diaphragm is between 0.5 μm and 2 μm; c. The diaphragm has excellent mechanical strength, and its breaking strength is not less than 5 MPa.